Characterization and Fertility Assessment of Soils of Mirzapur District of Eastern Uttar Pradesh for Sustainable Land Use Planning - Preeti Singh and Aradhana Thakur, Seema*, A.K. Ghosh, Sunita Yadav (Journal of the Indian Society of Soil Science, 2022)
Ten typical pedons representing major landforms in semi-arid and sub-tropical ecosystem of Mirzapur district of Uttar Pradesh viz., plains, mid lands and uplands developed from alluvium parent material under varying land uses were studied for their morphological characteristics, physical and chemical properties and soil classification. The colour of the soils ranged from light brown grey to brownish yellow and dark brown with a dominant hue of 10YR. These soils were acidic to moderately alkaline (pH 6.0 to 8.6) in reaction, non-saline, moderately deep to very deep and had isohyperthermic temperature and udic soil moisture regime. Texture and total organic carbon (TOC) ranged from loam to clay loam and 0.3 to 19.9 g kg-1, respectively. Soils were lower to medium range in phosphorus (4.0 to 18.0 kg ha-1) and available potassium (96 to 299 kg ha-1). All the pedons had ochric epipedon and underlain by cambic horizon (P3, P4, P7, P8, P9 and P10) within the control section and as such they come under order Inceptisols whereas P1, P2, P5 and P6 have argillic horizon so they come under order Alfisols. All soils of the study area fall in agricultural land under land capability classes III and IV having limitations of slope and erosion. On the basis of major soil constraints and potentials, suitable land use plan has been suggested.